Therapeutic Potential of Curcuma Longa and Its Constituents Role in the Treatment of Multiple Sclerosis - Prakash Pralhad Sarwade; Santosh Kumar S.R.; ., Yuvraj; Rohit Kumar; Navin Chandra Pant; Kavita Narayan Gaisamudre (Sarwade) (Asian Journal of Pharmaceutical Research and Development, 2024)
A neurodegenerative illness characterised by chronic inflammation and demyelinating symptoms, multiple sclerosis (MS) mostly affects young people's central nervous systems. The condition is complex and variable due to multiple environmental and genetic factors. A disorder mediated by the immune system is what it is. Symptoms of neurological dysfunction that last a few days or weeks and can be recovered are common in the early stages of the disease, which include clinically isolated syndrome and relapsing-remitting multiple sclerosis. Turmeric, whose scientific name is Curcuma longa Linn. (C. longa), is a member of the Zingiberaceae family of plants that has a rich history of use in traditional medicine. In Unani and Ayurvedic medicine, C. longa has been used topically for inflammation and ulcers, and internally for jaundice and liver blockage. Blood purification, asthma, haemorrhoids, bronchitis, tumours, wounds, indigestion, colds, dental problems, skin infections, and hepatic illnesses are all helped by its antiseptic properties. The crucial phase that starts this cascade is when Th17 enters the central nervous system (CNS) through the blood-brain barrier (BBB) through damaged tight junctions. Interleukin (IL)-17 and IL-22 attach to their BBB receptors, allowing the migration to proceed. Then symptoms of neuromuscular diseases, such as axonal degeneration, start to show themselves. The Zingiberaceae family plant Curcuma longa is the source of curcumin, the active ingredient in turmeric. There is hope for the treatment of multiple sclerosis (MS) thanks to recent findings about the properties of curcumin, namely its ability to suppress the release of proinflammatory cytokines. When it comes to treating MS, this study will look at curcumin's many features and major impacts.